Dietary Modification for Reproductive Health in Women With Polycystic Ovary Syndrome: A Systematic Review and Meta-Analysis - Shang, Yujie; Zhou, Huifang; He, Ruohan; Lu, Wentian (Frontiers in Endocrinology, 2021)
Objective: Diet has been reported as the first-line management of polycystic ovary syndrome (PCOS). However, the relationship between diet and fertility in PCOS is still controversial. This meta-analysis aimed to evaluate whether diet could promote reproductive health in women with PCOS while providing evidence-based nutrition advice for clinical practice. Methods: Seven databases, including Cochrane Central Register of Controlled Trials, PubMed, Embase, Web of Science, and some Chinese database, were searched up to January 31, 2021. Randomized controlled trials evaluating the effects of diet in women with PCOS were included. Based on a preregistered protocol (PROSPERO CRD42019140454), the systematic review was performed following the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines. Two reviewers made study selection, data extraction and bias assessment independently. Risk ratios and mean difference with 95% confidence intervals were assessed by a random-effects model. Statistical heterogeneity within comparisons was evaluated by Cochran’s Q test and quantified by the I-squared (I2) statistic. Results: Twenty RCTs with 1113 participants were included. Results showed diet significantly related to improved fertility outcomes (increasing clinical pregnancy, ovulation and menstrual regularity rate; reducing miscarriage rate), reproductive endocrine [increasing sex hormone-binding globulin (SHBG); decreasing Anti-Müllerian Hormone (AMH), free androgen index (FAI), total testosterone (T)] and clinical hyperandrogenism (hirsutism assessed by Ferriman-Gallwey score) in PCOS. Specifically, subgroup analyses indicated low-carbohydrate diets were superior in optimizing reproductive outcomes and calorie restriction was critical in ameliorating hyperandrogenism. Additionally, the positive effects were associated with the treatment duration. The longer the duration, the greater the improvement was. Conclusion: Overall, diet is an effective intervention for improving fertility health, thus professional and dynamic dietary advice should be offered to all PCOS patients, based on the changeable circumstances, personal needs and expectations of the individuals.